Islamic legal principles and intellectual property rights in the Gulf States / Nadia Naim. - Naim, Nadia (Middle Eastern & Islamic studies at Gerlach Press., 2023)
The book focuses on the relationship between Islamic law and intellectual property law and proposes groundbreaking alternatives to better support the growth of intellectual property in line with the Islamic moral economy. The author provides an overview of the development of intellectual property under Shariah principles in the Gulf States. She focuses on how the US and the EU have shaped the intellectual property regimes in the Gulf States, the WTO and WIPO in the pre-TRIPS era, and compliance with the minimum standards of the TRIPS Agreement. In addition, the impact of the TRIPS Plus standards and investorstate dispute settlement, as well as the implications for Gulf states of committing to further international investor agreements are examined. Innovative recommendations for an integrated approach to intellectual property law that incorporates the principles of Islamic commercial and financial law will be of interest to both academics and practitioners within and outside the region.